Innovation in physical testing equipment for karate junior kumite category - Manullang, Jujur Gunawan; Aliriad, Hilmy; Purba, Pangondian Hotliber; Da'i, Mohamad (Journal Sport Area, 2024)
Background Problems: The lack of instruments suited to the unique needs of karate athletes in the junior Kumite category poses a significant challenge. Research Objectives: This study aims to develop a physical testing tool specifically designed to measure the physical abilities of junior athletes in the Kumite category. Methods:  The research method used developmental research to test the effectiveness of the product in the form of a karate physical test instrument. The data analysis was obtained from the results of interviews, observations, field notes, and describes the percentage of success of the trial product both in terms of process and research results starting from the planning, implementation, reflection, evaluation stages in the form of psychomotor, affective, cognitive data, and physical test results. Furthermore, the data from the physical test results were analysed using SPSS version 23 statistical techniques to identify the relationship between physical test results and performance in Kumite. Findings and Results: The results of this study indicated that the newly developed physical test instrument can provide a more specific measurement of the physical abilities of junior karate athletes in the Kumite category. In addition, the results also provided greater insight into the physical factors that influence performance in Kumite matches. By providing a more effective tool and increasing the understanding of the relationship between physical attributes and competitive performance. Conclusion: The implication of this study is that a scientific approach using physical measures provides a valuable contribution to the development of a selection system and the coaching of junior karate athletes. Thus, this study makes an important contribution to the development of the performance of junior karate athletes and improves the efficiency of their selection and coaching processes.